The determinants and consequences of economic vulnerability among urban elderly Nigerians - Adisa, Olumide Oludolapo (2016)
In rapidly urbanising Sub-Saharan African contexts, not much is known about the economic vulnerability of elderly people and its consequences. Dominant international institutions have indicated that the economic situation of elderly people in developing countries is precarious, especially where high levels of poverty and minimal social safety nets are the norm. As a consequence, the impact of economic vulnerability can be quite punishing on disadvantaged households with an ageing elderly person. Yet, the case of urban elderly Nigerians has thus far remained largely unresearched. This thesis represents a quantitative investigation of economic vulnerability amongst urban elderly Nigerians and its health-related consequences, examined through a consumption allocation welfare measure. It draws on economic, gerontological, and sociological perspectives to undertake this task. The key drivers of economic vulnerability and resulting consequences are likely to be complex and varied. Urban Elderly Nigerians may be economically vulnerable because they possess certain pre-disposing characteristics. This study is concerned with investigating these associated determinants of economic vulnerability amongst urban elderly Nigerians using a recent nationally representative household survey—the Nigerian General Household Panel Survey (NGHPS), which was collected by the National Bureau of Statistics in 2010. The first part of the study examines the determinants of economic vulnerability, through the use of a consumption allocation model. The findings of this study reveal that the age of the household head, household size, household structure, and regional location, are key determinants of economic vulnerability amongst urban elderly households in Nigeria. As a consequence, does economic vulnerability (represented by consumption allocation) influence health status and spending amongst elderly Nigerian households? I extracted useful data from the NGHPS to address this pertinent question. This is the second part of the study. The findings suggest that economic vulnerability is strongly related to health status and health spending. This thesis highlights key methodological challenges in using a secondary data source to study economic vulnerability amongst elderly people in a developing country context. The study also offers some policy options to tackle economic vulnerability among elderly households in urban Nigeria, and its health-related consequences.